POLA PERUBAHAN HARIAN SUHU AIR DAN KECEPATAN ARUS DI SEKITAR GUNUNG API BAWAH LAUT MAHENGETANG - Stivano Mamarama; Armstrong Sompotan; Farly Tumimomor (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2020)
Indonesia an archipelago with 70% of the territorial waters stretching from the western end of Sumatra Island to the east of the Papua region, with the characteristic of the vast ocean of underwater structures in the Indonesian archipelago is also important to be discussed deeper. For that the underwater volcano research is very rare. This undersea research has been implemented and is a collaborative research study with DRPM's beginner lecturer SCHEME research with the title of Master of Umbrella research